Structural Imbalance and Life-Cycle Cost Coverage in Vertical Greenery Systems: A Systematic Literature Review - Phatthanaphan, Nitchaya; Wongvorachan, Tarid; Wutisun, Duangkamon; Singkham, Sathirat; Petsirasan, Sippakorn; Thampanichwat, Chaniporn; Bunyarittikit, Suphat; Sirirat, Sanawete (My University, 2026)
Vertical greenery systems (VGS), including vertical gardens (VG) and green façades (GF), are increasingly promoted as nature-based solutions for sustainable urban development. Despite their environmental benefits, economic evaluation remains fragmented, particularly within a life-cycle cost (LCC) perspective. This study conducts a systematic literature review to examine the structural configuration of cost-related research on VGS within an LCC framework. Following the PRISMA protocol, 136 peer-reviewed articles published between 2021 and 2025 were identified through a structured search of the ScienceDirect database and retained as the analytical dataset. Bibliometric mapping, thematic classification, and co-occurrence analysis were applied to assess publication patterns, the distribution of cost components, and reporting structures. Five principal cost categories were identified: Installation and Operation, Maintenance, Consumables, Materials and Manufacturing, and Design. The results reveal a pronounced concentration on installation and maintenance costs, while design-phase economics and comprehensive LCC integration remain marginal. Most studies address only one or two cost categories, indicating structural fragmentation. In addition, heterogeneous reporting units and inconsistent contextual descriptors constrain cross-study comparability and cumulative synthesis. Collectively, the findings demonstrate that although cost research on VGS is expanding, it has not yet achieved methodological maturity within a standardized LCC framework. Advancing harmonized cost-reporting protocols and integrated life-cycle modeling is therefore essential to support robust economic evaluation and informed implementation of VGS in sustainable built environments.
Keywords: cost analysis; life-cycle cost; sustainable construction; systematic review; vertical greenery systems